Analisis Pengaruh Rasio Keuangan dan Faktor Ekonomi Makro Terhadap Financial Distress Pada Perusahaan Manufaktur - Fani Febriana Putri; Haifa Haifa; Nanda Widaninggar (Institut Teknologi dan Sains Mandala, 2022)
This study aims to analyze financial ratios and macroeconomic factors on financial distress in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2019. The data used in this study were obtained from the company's annual financial statements. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The sample selection technique used was purposive sampling and obtained 18 food and beverage sub-sector manufacturing companies with the 2016-2019 research period. The data analysis method in this study was logistic regression analysis. Based on the data analysis, it is concluded that the liquidity ratio as measured by the Current Ratio (CR), inflation and exchange rates have no effect on financial distress while the profitability ratio as measured by Return on Equity (ROE) and solvency ratio as measured by Debt to Total Assets Ratio (DAR) has an effect on financial distress.